A SWOT-AHP APPLICATION USING FUZZY CONCEPT: E-GOVERNMENT IN TURKEY - Kahraman, Cengiz; Demirel, Nihan Cetin; Demirel, Tufan; Ates, Nuefer Yasin (SPRINGER, 2008)
E-government refers to the delivery of information and services online via the Internet. Many governmental units across the world have embraced the digital revolution and placed a wide range of materials on the web, from publications to databases. The purpose of this study is to evaluate and to determine the alternative strategies for c-government applications in Turkey. We use the strengths, weaknesses, opportunities, and threats (SWOT) approach in combination with the crisp and fuzzy analytic hierarchy process (AHP) to achieve this task. The strategies have been prioritized by using both methods comparatively and sensitivity analyses of the obtained results have been presented.
Keywords: Outranking; fuzzy outranking relation; pair-wise comparison; e-government; SWOT; analytic hierarchy process; strategic planning; sensitivity analysis; SERVICES; CITIES; MODEL; Mathematics